EFEKTIVITAS KOMBINASI EKSTRAK ETANOL DAUN AFRIKA (Gymnanthemum amygdalinum Del.) DAN EKSTRAK ETANOL DAUN KELAPA SAWIT(Elaeis guineensis Jacq.)TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH - Rani Ardiani (Jurnal Penelitian Farmasi & Herbal, 2020)
African leaves (Gymnanthemum amygdalinum Del.) And palm oil leaves (Elaeis guineensis Jacq.) Have been shown to contain flavonoid compounds, where they are efficacious as antidiabetic. This study aims to determine the combined effectivenessof ethanol extract of African leaves and palm oil leaves as antidiabetic in white rats.The study was conducted using the method of alloxan induction and measured using glucometers. 15 animals were divided into 5 groups, namely negative control, positive control, group I combination of ethanol extract of african leaves and oil palm leaves 25 + 25 mg/kg weight, group II combination of ethanol extract of african leaves and palm oil leaves of 50 + 50 mg/kg weight, group III combination of ethanol extract of African leaves and leaves of oil palm 100 + 100 mg/kg weight for 15 days. Examination of antidiabetic effects is done by comparing the KGD value of the rats before and after treatment. The results of this study indicate that the three doses have antidiabetic effects. Data on the differences in the KGD of rats were carried out statistically using the Shapiro Wilk normality test and the Levene homogeneity test and continued with the ANOVA test. The conclusion of this study is that the dose is the most effective in reducing blood glucose levels in rats, which is a dose of 100 + 100 mg/dl because it mostly decreases blood glucose levels.